The Persuasive Propositions in Argumentation: A Perspective in Heritage Linguistics - Alzabin, Emad Ahmad (Dirasat: Human and Social Sciences, 2023)
Objectives: This study aims at investigating the concept of "persuasive issues " in the applications of heritage linguistics, and to report the distinctive chapters of persuasive issues from the rest of the proven argumentative issues according to the insight of linguists in our heritage. Then reveal the laws of" persuasive cases" and the rules to produce knowledge about them or say: about determining the rank of these cases in the Hajj ladder. Methodology: The study employed a descriptive survey to analyze the efforts included in the works of many scholars concerned with the systems of argumentative theories in this heritage spot. The analysis began by revealing the core of the persuasive issue, deciding the characteristics of these issues and their distinct chapters, then revealing their most prominent conditions and the rules. Results: This study reveals that persuasive issues are public ones that address the space of the psychological acceptance more than the requirements of complex mental analysis. They don’t produce a definitive knowledge, because they consist mostly of non-evidential elements, and they may take the form of linguistic fallacies. Considering the logical structure of persuasive issues indicates the network of mental procedures that form the inner linguistic universe. Conclusions: Persuasive propositions as reflected in the heritage linguistics must be given their due consideration as they will contribute to the development of both linguistic argumentative and methodological semantic lesson.